Gaining Momentum in Peruvian Agriculture : Opportunities to Increase Productivity and Enhance Competitiveness - World Bank (World Bank, Lima, 2017)
What is the future for agriculture in Peru? Once the principal source of employment and income for much of the population, Peru’s agricultural sector has declined in importance as the national economy has grown and urbanized. Economic activity in the sector has continued to grow, but economic activity in other sectors has grown more rapidly, leaving agriculture to make up an ever smaller share of the overall economy. The future of Peruvian agriculture should concern policy makers, for at least five reasons. First, agriculture makes up an important part of the economy, so if agricultural growth decelerates, overall growth will suffer. Second, an expanding agricultural sector diversifies Peru’s economy and reduces dependence on extractives, so if the agricultural sector contracts relative to other sectors, economic growth could become more volatile. Third, agriculture-led growth is good for the poor, so if agricultural growth slows, an important means of reducing poverty will be lost. Fourth, Peru relies on food imports to make up production shortfalls, so if agricultural production fails to keep pace with population growth, national food security could be threatened. Fifth, climate-smart agricultural practices can play a major role in reducing greenhouse gas emissions and sequestering carbon, so if future agricultural practices are not climate smart, an important opportunity to help mitigate climate change will be missed. This report synthesizes current knowledge about the ongoing transformation of Peru’s agriculture and food system, assesses the recent performance of the agriculture sector with an emphasis on productivity and competitiveness, and highlights opportunities for enhancing the future contribution of the agriculture sector toward meeting the country’s development challenges.